2014
DOI: 10.1002/aenm.201400981
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐ and Mesoporous Carbide‐Derived Carbon–Selenium Cathodes for High‐Performance Lithium Selenium Batteries

Abstract: ion battery (LIB) chemistry. Such LIB cells offer signifi cantly higher energy density than lead-acid or nickel-metal hydride batteries and reasonably good cycle stability. [ 4 ] However there is a plenty of room for improvement in various aspects, such as cost, safety, energy density, power, thermal, and cycling stabilities. [ 5 ] One strategy to improve LIB is to employ higher capacity cathode materials and, in some cases, simultaneously replace graphite anodes with higher capacity Li electrodes. There has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
100
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(103 citation statements)
references
References 37 publications
2
100
0
1
Order By: Relevance
“…Issues occurred as S, Se cathode also has to face the poor cycle performance and low Coulombic efficiency (CE) caused by the dissolution of high-order polyselenides. [15][16][17] In order to modify the electrochemical properties of Li-Se cells, great efforts have been made as follows. Guo's group successfully encapsulated Se within a typical ordered mesoporous carbon in the form of cyclic Se 8 17 and hierarchically micro-/mesoporous carbon spheres.…”
Section: Introductionmentioning
confidence: 99%
“…Issues occurred as S, Se cathode also has to face the poor cycle performance and low Coulombic efficiency (CE) caused by the dissolution of high-order polyselenides. [15][16][17] In order to modify the electrochemical properties of Li-Se cells, great efforts have been made as follows. Guo's group successfully encapsulated Se within a typical ordered mesoporous carbon in the form of cyclic Se 8 17 and hierarchically micro-/mesoporous carbon spheres.…”
Section: Introductionmentioning
confidence: 99%
“…2(a), right]. 22,39 Besides S, the chalcogenides (Li 2 S, Se, Li 2 Se, Te, and Li 2 Te) are similarly suffering from dissolution of intermediate reaction products (polychalcogenides) in electrolytes, 23,28,[39][40][41][42][43][44] which results in capacity loss, shuttle, and formation of insulating layers. [21][22][23]43,45 Similar to Li-chalcogen batteries, recent studies on various MHs also reported serious challenges of metal and halide dissolution during electrochemical conversion reactions.…”
mentioning
confidence: 99%
“…As such, if cathode dissolution and unfavorable interactions between active materials and electrolyte are avoided, conversion cathodes should be able to show very long cycle stability in cells. [16][17][18][19][20][21][22][23][24][25][26][46][47][48][49][50] The in situ CEI protection on the surface of the conversion cathodes has a promise to overcome such challenges as shown in Fig. 3(b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zeng et al [28] confined Se in the matrix of porous carbon nanofibers (PCNFs), which can deliver a reversible capacity of 516 mAh/g after 900 cycles without any capacity loss at 0.5 A/g and 306 mAh/g at 4 A/g. Lee et al [29] prepared nanocomposites of Se and ordered mesoporous silicon carbide-derived carbon (OM-SiC-CDC), whose the discharge capacity in 7 M electrolyte retained approximately 96.4 % of its initial capacity (around 420 mAh/g). Li et al [30] confined Se in metal complex-derived porous carbon (Se/MnMC-B), which exhibited a capacity of 580 mAh/g after 1000 cycles at 1C.…”
Section: Introductionmentioning
confidence: 98%